Proses Berpikir Nabi Ibrahim as. Melalui Dialog dengan Tuhan dalam al-Qur’an - Syahputra, Afrizal El Adzim (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
Thinking and dialogue is an inseparable part of life. Various studies about the Prophet Ibrahim as. have been found, but the process of deepening related to thinking process through the dialogue of Prophet Ibrahim as. to Allah Swt is still limited to be discovered. This article is structured to reveal the way of thinking of Prophet Ibrahim as. in his efforts to dialogue with Allah Swt. This paper was prepared using the literature research method, which in this case uses the Qur'an as a primary reference and books, commentaries, and soft ware applications as a secondary reference source. The results show that the dialogue carried out by Prophet Ibrahim as. involves a process of critical thinking, rational thinking, accompanied by curiosity and based on faith and devotion to Allah Swt. Prophet Ibrahim as. who had previously been at the level of "Ilm al-Yaqin", was able to reach the level of "Haqq al-Yaqin". Through this article, it is expected to be able to open up insights for people to think and dialogue in solving life's problems. Of course in this case thinking and dialogue in this life is essentially intended to draw closer to Allah Swt at the level of Haqq al-Yaqin.